Green synthesis and characterization of silver nanoparticles using Cassia fistula and assessment of its in vitro anti diabetic activity - J Bagyalakshmi; S Siva Sivakumaran; K Priya; R Swathika (Global Journal of Allergy - Peertechz Publications, 2023)
The study aimed to synthesize silver nanoparticles with anti-diabetic properties using Cassia fistula bark extract using a one-step biological method. The methanolic bark extract was mixed with a 1mm silver nitrate solution, and the resulting silver nanoparticles were characterized using various methods such as visual examination, UV visible spectroscopy, FTIR spectroscopy, Field Emission Scanning Electron Microscopy, in vitro Dissolution Study, Particle Size determination, and Zeta Potential determination.  The green synthesis of silver nanoparticles using Cassia fistula bark extract aimed to develop a novel drug delivery system with herbal drugs to reduce side effects. The plasmon band in the silver nanoparticles was found to be 425 nm, and the FTIR study revealed a higher presence of Hydroxyl and carboxylic groups as reducing and stabilizing agents.  The drug entrapment was found to be 61.5%, the particle size was 148.5 nm and the polydispersity index was 0.243. The zeta potential was measured to be -0.1 mV, indicating no stabilization of the silver nanoparticles. The FESEM analysis showed the synthesized silver nanoparticles to be spherical and oval in shape. This biological method is eco-friendly and cost-effective, making it a promising alternative to traditional chemical/stabilizing agents.